Microbiological quality of ice used to refrigerate foods - Falcão, J. P. [UNESP]; Dias, A. M G; Correa, E. F. [UNESP]; Falcão, D. P. [UNESP] (Elsevier, 2002)
Ice used for human consumption or to refrigerate foods can be contaminated with pathogenic microorganisms and may become a vehicle for human infection. To evaluate the microbiological content of commercial ice and ice used to refrigerate fish and seafood, 60 ice samples collected at six different retail points in the city of Araraquara, SP, Brazil, were studied. The following parameters were determined: total plate counts (37° C and 4° C), most probable number (MPN) for total coliforms, fecal coliforms and Escherichia coli, presence of Salmonella spp., Shigella spp., Yersinia spp., E. coli, Vibrio cholerae and Aeromonas spp.. Results suggested poor hygienic conditions of ice production due to the presence of indicator micro-organisms. Fifty strains of E. coli of different serotypes, as well as one Y. enterocolitica biotype 1, serogroup 0:5, 27 and phage type Xz (Ye 1/05,27/Xz) and one Salmonella Enteritidis phage type 1 (PT1) were isolated. Aeromonas spp., Shigella spp. and V. cholerae were not detected. The presence of high numbers of coliforms, heterotrophic indicator micro-organisms and pathogenic strains suggested that commercial ice and ice used to refrigerate fish and seafood may rep resent a potential hazard to the consumer in our community. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Aeromonas; Enteritidis; Escherichia coli; Salmonella; Salmonella enteritidis; Shigella; Vibrio cholerae; Yersinia enterocolitica